Iodine and goitrogens intakes among menopausal women in calcareous region - Mutalazimah, Mutalazimah; Mardiyati, Nur Lathifah; Isnaeni, Farida Nur; Puspitasari, Dyah Intan (Intelektual Pustaka Media Utama, 2025)
Wonogiri Regency, Indonesia, is a calcareous mountainous region which has limitations in terms of iodine content in soil and water. Kismantoro is one of the Sub-districts in the regency with severe iodine deficiency. This condition is related to the intake of iodine and factors that inhibit the intake of iodine such as goitrogens. This causal-comparative study was conducted to determine the difference of iodine and goitrogenic foods intakes among menopausal women in Kismantoro Sub-district. A total of 307 menopausal women were taken randomly. Iodine intake as well as goitrogens were measured using the semi quantitative-food frequency questionnaire (SQ-FFQ). There was no difference in the percentage of recommended dietary allowance (RDA) for iodine intake (p=0.857) and goitrogens intake (p=0.084) among the menopausal women, but there were differences in energy, protein, carbohydrate, and fat intake (p<0.001) respectively. In addition, the prevalence of goiter was 10.4% which did not differ in the premenopausal, perimenopausal and postmenopausal groups (p=0.227). However, it was found that most menopausal women had insufficient iodine intake (71.3%) and frequent goitrogenic foods intake (68.7%). Thus, a synergistic manner between stakeholders is still needed to improve the variation of iodine food sources while consume less goitrogens in the area.